Translating the MAM Model of Psychosis to Humans - Modinos, Gemma (Trends Neurosci, 2014)
Elevated dopamine function and alterations in the medial temporal lobe structure and function (MTL) are two of the most robust findings in schizophrenia, but how interactions between these abnormalities underlie the onset of psychosis is unclear. Although several preclinical models of psychosis have been proposed, the methylazoxymethanol acetate (MAM) rodent model provides a mechanistic account linking these two clinical observations. The model proposes that psychosis develops as a result of a perturbation of MTL function, leading to elevated striatal dopamine dysfunction. We review a number of recent neuroimaging studies that examine components of the putative model in people with an ultra high risk (UHR) of psychosis. Whilst data from these studies are broadly consistent with the MAM model, that the potential for comparing various kinds of neurobiological data across animal and human studies imposes some limitations on what can be inferred from these data. Going forward, longitudinal studies are needed to explicitly test the model’s predictions in UHR populations.